Analysis of tapping process in three types of cast iron. Issue 5 (February 2016) - Pereira, Igor; Silva, Marcio; Cunha, Daniel; Sales, Wisley
Abstract The main objective of this work is to investigate the tapping operation of cast iron when varying the cutting speed and the method of application of cutting fluid, monitoring tool wear, torque, and axial force during the operation. Two types of gray cast iron were evaluated: CrCuSn alloy, FC 250; CrCuSnMo alloy, FC 300, and compacted graphite iron machine tool, FV 350. Tests were performed at two lubrication/cooling conditions: in the first one, it was applied an emulsion of water and oil; in the second one, the fluid was applied in minimal quantity (MQF), at pressure of 6.0 bar and intermittent spray at a frequency of 1 pulse/s, resulting in a flow rate of 30 ml/h. For MQF condition, a vegetable oil was used. Torque, axial forces, and tool wear were measured during the operation. Statistical analysis showed that the cutting speed was the parameter that most influences the torque, followed by the cutting fluid and the material hardness.